Concevoir pour des activités instrumentées par des chatbots - Marion Gras Gentiletti; Gaëtan Bourmaud; Myriam Fréjus; Françoise Decortis (Activités, 2022)
In what way are chatbots new resources for humans? What are the conditions for their successful implementation? How do chatbots transform human activity? To answer these questions, this paper investigates how four chatbots were implemented and utilized in a professional context based on real user activity. We first show that the current design approach does not take sufficient account of the real activity and its multiple determinants, or of the users' point of view on their activity. Yet these interactive devices participate in a pre-existing socio-technical system made up of a diversity of subjects engaged in activities with multiple purposes. Through the prism of instrumental geneses, we therefore propose to identify how these chatbots can help or hinder human activity, so as to document, for design purposes, the conditions leading to the emergence of chatbot uses. After a synthetic presentation of the empirical results, we discuss the relevance of the instrumental approach when characterizing the contributions and limitations of chatbots. Finally, we argue that a design perspective supporting the postulate of human-machine asymmetry is prolific in supporting a design approach that is more focused on human power to act than on innovation.